Oral immunotherapy with enteric-coated capsules for allergic rhinitis caused by house dust mites - Zhang, Han-Zhong; Xie, Wei; Zhou, Wen-Cheng; Chen, Jian; Wang, Ying; Zhu, Yuan-Yuan; Wen, Ting-Huan; Cheng, Lei (Frontiers in Allergy, 2024)
Oral immunotherapy (OIT) is a promising allergen-specific approach in the management of food allergy; however, studies on OIT for allergic rhinitis (AR) have rarely been reported. The purpose of this study is to evaluate the efficacy and safety of OIT using enteric-coated capsules for AR induced by house dust mites. A total of 49 patients with AR were enrolled, including 25 who received subcutaneous immunotherapy (SCIT) and 24 who received OIT. The clinical efficacy and safety in both groups were evaluated. After one year of treatment, both SCIT and OIT demonstrated significant therapeutic effects. OIT was found to be more effective than SCIT in reducing the total AR symptom score and improving the results of nasal provocation tests. Local and systemic adverse reactions were observed in the SCIT group, while none were reported in the OIT group. OIT is an effective and safe treatment for mite-induced AR.